Hubungan Pengetahuan Dan Sikap Bidan Terhadap Kepatuhan Penggunaan Alat Pelindung Diri Saat Persalinan : Systematic Review - Hakim, Dwi Ratnawaty; Windusari, Yuanita; Sari, Novrika; Fajar, Nur Alam (Health Information : Jurnal Penelitian, 2023)
The risk of infection transmission during childbirth to midwives is still observed to be high. Prevention by using standards personal protective equipment tends to be less adhered to by midwives. The compliance is associated with the level of knowledge and attitudes of midwives. This study will discuss the relationship between knowledge and attitudes of midwives as predisposing factors for compliance of PPE during childbirth. This systematic literature review (SLR) uses Google Scholar and PUBMED in accordance with keywords and PRISMA guidelines. Data was extracted into Microsoft Excel and analyzed descriptively. 9 cross-sectional articles included in this SLR and most of the studies stated that the knowledge and attitudes of midwives were significantly related to compliance of PPE during childbirth assistance. Knowledge will be a control for midwives to have a positive attitude, especially in wearing complete PPE. Several studies also report that these two factors don’t relate each other because it can be influenced by low levels of knowledge and attitudes as well as external factors such as discomfort when wearing PPE. Therefore, the knowledge and attitude factors of a midwife are still dominant in influencing the level of compliance of PPE during childbirth assistance.